Copper diffusion rates and hopping pathways in superionic Cu2Se. (15th August 2021) - Nazrul Islam, Sheik Md Kazi; Mayank, Prince; Ouyang, Yulou; Chen, Jie; Sagotra, Arun.K.; Li, Meng; Cortie, Michael B.; Mole, Richard; Cazorla, Claudio; Yu, Dehong; Wang, Xiaolin; Robinson, Robert A.; et al.
Abstract: The ultra-low thermal conductivity of Cu2 Se is well established, but so far there is no consensus on the underlying mechanism. One proposal is that the fast-ionic diffusion of copper suppresses the acoustic phonons. The diffusion coefficients reported previously, however, differ by two orders of magnitude between the various studies and it remains unclear whether the diffusion is fast enough to impact the heat-bearing phonons. Here, a two-fold approach is used to accurately re-determine the diffusion rates. Ab-initio molecular dynamics simulations, incorporating landmark analysis techniques, were closely compared with experimental quasielastic/inelastic neutron scattering. Reasonable agreement was found between these approaches, consistent with a diffusion coefficient of 3.1 ± 1.3 × 10 −5 cm 2 .s −1 at 675 K and an activation barrier of 140 ± 60 meV. The hopping mechanism includes short 2 Å hops between tetrahedral and interstitial octahedral sites. This process forms dynamic Frenkel defects. Despite the latter processes, there is no major loss of the phonon mode intensity in the superionic state, and there is no strong correlation between the phonon spectra and the increased diffusion rates. Instead, intrinsic anharmonic phonon interactions appear to dictate the thermal conductivity above and below the superionic transition, and there is only subtle mode broadening associated with the monoclinic-cubic structural transition point, with the phonon density-of-states remaining almost constant at higher temperatures. Graphical Abstract: Image, graphical abstract